2020
DOI: 10.1080/15623599.2020.1735610
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the gaps in construction megaproject management research: a bibliographic analysis

Abstract: The worldwide growth of megaprojects has triggered an increasing number of academic publications in the past few decades. However, there are few studies drawing the whole picture of construction megaproject management. This study aims to investigate the status and identify research implications of construction megaproject management by conducting a systematic review. A total of 155 journal articles in 2007-2018 were identified and analysed, mainly using a bibliographic analysis on annual circulation, major jou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 87 publications
2
20
0
3
Order By: Relevance
“…Between 2000 and 2010, several prominent project and engineering management journals included only 4.7 % of 85 studies examining megaproject complexities (Hu, Chan, Le & Jin, 2015). This result is consistent with a study conducted by Wang, Chan, He, and Xu (2020), who noted a gap in megaproject studies conducted between 2007 and 2018, identifying that only 7.2 % of 145 studies focused on complexity management.…”
Section: Complexity and Megaprojectsupporting
confidence: 83%
“…Between 2000 and 2010, several prominent project and engineering management journals included only 4.7 % of 85 studies examining megaproject complexities (Hu, Chan, Le & Jin, 2015). This result is consistent with a study conducted by Wang, Chan, He, and Xu (2020), who noted a gap in megaproject studies conducted between 2007 and 2018, identifying that only 7.2 % of 145 studies focused on complexity management.…”
Section: Complexity and Megaprojectsupporting
confidence: 83%
“…These include social network analysis [138], system dynamic models [76], and partial least squares structural equation models. By applying these newly developed mathematical techniques and theoretical approaches, the multiple elements, complexity, and dynamics of megaproject management can be explained to better advance the research on megaproject management theory [34,138]. Therefore, the increasing trend of research will become more apparent in the future by adopting different research approaches in megaproject management.…”
Section: Categories Of the Research Methods To The Identified Publicationsmentioning
confidence: 99%
“…It can avoid the impalpable and arbitrary result. Therefore, the analysis showed that the identified papers could be categorized into five clusters: megaproject management in general [29,[116][117][118][119], megaproject sustainability [27,34,[120][121][122][123], megaproject governance [22,[124][125][126][127][128][129], megaproject investment and finance [44,48,92,[130][131][132], and megaproject risk management [95,112,[133][134][135][136]. When the topic of a paper was related to multiple clusters, the paper was classified into the most closely related cluster.…”
Section: Research Topics Of the Identified Papers In Megaproject Management Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…All these applications are capable of creating and depicting basic bibliometric networks; however, VOSviewer was selected for our study due to the ease of use, easy interpretability of networks through visualization, and the popularity of the software in engineering and management research (Tariq et al 2020). Science mapping analysis has already been employed in different research areas, such as construction safety (Akinlolu et al 2020), megaprojects (Wang et al 2020), and acoustic-based leak localization (Hu et al 2021), which has yielded meaningful research outcomes including (1) working linkages and measurements between researchers, countries, and organizations and (2) preliminary ideas on the existing research themes and future research directions (Tariq et al 2020). In our study, VOSviewer was used for science mapping of journal sources, contributing countries, and popular keywords.…”
Section: Science Mapping Analysismentioning
confidence: 99%